Visualization of prostatic nerves by polarization-sensitive optical coherence tomography - Yoon, Yeoreum (Biomed Opt Express, 2016)
Preservation of prostatic nerves is critical to recovery of a man’s sexual potency after radical prostatectomy. A real-time imaging method of prostatic nerves will be helpful for nerve-sparing radical prostatectomy (NSRP). Polarization-sensitive optical coherence tomography (PS-OCT), which provides both structural and birefringent information of tissue, was applied for detection of prostatic nerves in both rat and human prostate specimens, ex vivo. PS-OCT imaging of rat prostate specimens visualized highly scattering and birefringent fibrous structures superficially, and these birefringent structures were confirmed to be nerves by histology or multiphoton microscopy (MPM). PS-OCT could easily distinguish these birefringent structures from surrounding other tissue compartments such as prostatic glands and fats. PS-OCT imaging of human prostatectomy specimens visualized two different birefringent structures, appearing fibrous and sheet-like. The fibrous ones were confirmed to be nerves by histology, and the sheet-like ones were considered to be fascias surrounding the human prostate. PS-OCT imaging of human prostatectomy specimens along the perimeter showed spatial variation in the amount of birefringent fibrous structures which was consistent with anatomy. These results demonstrate the feasibility of PS-OCT for detection of prostatic nerves, and this study will provide a basis for intraoperative use of PS-OCT.